Evaluation and Assessment of Capability of Hydrograph Model of Instantaneous Geomorphology Unit in Simulating Flood Hydrograph of Minab River Basin - Masoumeh Asadi; Iraj Jabbari; Homayoon Hesadi (جغرافیا و توسعه, 2022)
Accurate prediction of floods is especially important in arid areas with more irregularities and intensities. Lack of hydrometric stations in these areas of our country, along with the important advantage of the GIUH model, which allows the simulation of precipitation-runoff of a basin with the least information data, led the researchers to evaluate the above model in the basin. Consider the catchment of Minab as their goal. The quantitative values ​​of each of the geomorphological parameters of the GIUH model, the most important of which are the bifurcation ratio, length ratio and area ratio, have been calculated using GIS technology and with the help of  HECGeoHMS add-on. In ranking waterways, the Strahler method was used as a basis. The hydrograph model of the geomorphology unit in the study basin has had acceptable results according to the calculated average error equivalent to 17.22% for the peak discharge of 4 selected events. However, in estimating the peak occurrence time, the amount of error is higher and in all events, the peak discharge time is less than the real time. In addition, the results of this model in the same basin under study also provided acceptable results with an average error rate of about 30% in calculating the peak discharge. The GIUH in Minab catchment has had acceptable results according to the mean error calculated for the peak discharge of 4 selected events. Therefore, it is possible to achieve the desired results from this model in similar conditions and by applying changes.